PENGARUH MOTIVASI PERJALANAN TERHADAP PENINGKATAN KUALITAS HIDUP WISATAWAN DOMESTIK DALAM MELAKUKAN PERJALANAN WISATA SPIRITUAL ( STUDI KASUS PADA PESERTA TIRTA YATRA KE INDIA) - Septia Fitriani, Kadek; Made Artajaya (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2025)
Tourism is a traveling activity that involves several aspects, such as individuals, activities and facilities. One type of tourism that people want to do is spiritual tourism. This study involved participants who bought pilgrim packages at Lila Travel using casual associative research with quantitative techniques, the primary data in this study were the results of a questionnaire involving 118 respondents, the secondary data in this study were sourced from books and journals. The data analysis technique in this study uses the SEM PLS analysis method and validity and reliability tests. The results of this study indicate that simultaneously travel motivation and spiritual tourism experience have a positive and significant effect on the life satisfaction of tourists who have carried out spiritual tourism trips with lila travel. Further researchers are advised to be able to add other variables that are not contained in this study in order to increase new knowledge and insights. Keywords : Travel Motivation, Traveler Life Satisfaction, Spiritual Tourism